Factores sociodemográficos y depresión en adultos mayores, Curgos 2018 - Palomino Mauricio, Roxana Karina (2019)
The present quantitative, descriptive, correlational, cross-sectional investigation was carried out in a health center, district of Curgos - province of Sánchez Carrión, year 2018; in order to determine the relationship between sociodemographic factors and the level of depression in adults over 60 to 80 years. The sample consisted of 120 older adults. The questionnaire was used to collect data: perception of family functionality and the geriatric depression scale of Yesavage. The results were presented in single and double entry tables, the information was processed and analyzed through the "chi-square" statistical test. It was found that the highest percentage (34.2%) were older adults with dysfunctional families, of which 20.8% were women, 21.7% were between 60 and 69 years of age; followed by (28.3%) with severely dysfunctional family, being 17.5% women, 19.2% were between 60 to 69 years of age; (19.2%) were older adults with moderately functional families, 10.0% were between 60 and 69 years of age. Only (18.3%) were older adults with a functional family, 15.0% were women and 11.7% were between 60 and 69 years of age. Regarding the level of depression, the highest percentage (37.5%) of older adults had severe depression, followed by moderate depression (29.2%), mild depression (20%) and 13.3% without depression. Concluding that there is a statistically significant relationship (p <0.05) between sociodemographic factors: Degree of family functionality, sex and age with the level of depression in older adults.